QrPay parking system - Tee, Ken Lee (2019)
The current public parking payment method has always been a great issue for years. Many problems including faulty machine, lack of coupon agent have troublesome the people who are using the parking space. Many experts have created some applications to overcome the same issues in different area. However, there are still some inadequate occurred in the current existing applications. QrPay Parking System is proposed to handle the parking payment issues occurred in Kuantan, Pahang with a better way. The main idea of QrPay Parking System is the user can locate the parking lot with their mobile device by scanning the QR code attached at the parking lots. The user can make their parking payment through the mobile application where the system will automatically calculate the amount for them based on the durations they spent on the parking session. This system will be developed by using the Mobile-D approach which is one of the general Agile methodologies. The development of the system will go through five different phase which we will discuss in this report. This project is targeted to the local authority and the public figures in Kuantan, Pahang to have a better experience on using the public parking spaces. This project is implemented by using Visual Studio including Xamarin.Forms and Windows Form. The interface design is easy for user to navigate and is created based on the Software Requirements Specification (SRS). All the functions available are visualized in Use Case and Sequence Diagram. For development purpose, all the classes and data structure are implemented based on Software Design Document (SDD). 30 users have been asked to perform user acceptance test (UAT) on the applications created and the feedback have been summarized in the UAT document. By creating this system, the public user can perform payment for their parking session in a more convenient way, which by scanning the attached QR Code.